Participação em associação de pequenos produtores: dilemas da administração coletiva - Souza, Maria de Lourdes Oliveira (1995)
This research was focused on the participatory management procedures used by the Peasants Association of Poço Fundo, in Southern Minas Gerais. The Association is atype of organization that, without any governmental support, is trying to attain better conditions of life for local peasants, based upon aparticipatory praxis that combines both short and long run actions. This junction increases the Association's possibilities of economical, social, political, and cultural accomplishments. For example, when the Association's directors are dealing área dealing with commercialization problems, at the same time and in a participatory way, they attempt to link this question to its deep causes and to other related matters that affect agricultural small production in general. Both the Association's formal leadership and the externai advisors área committed to an educational process wherein all members can have the opportunity to decide upon the Association's future. The research shows also the need to develop theories of agricultural administration related to this type of organization, for example, as regards appropriate organizational structures. A peasants association with collective objetives cannot be managed like a private business enterprise.